An Analysis of the Relationship Between Allah Centeredness and Moral Disengagement in terms of Some Variables - Nurgül Bulut; Ahmet Celalettin Güneş; Hatice Ayar (Darulfunun Ilahiyat)
The study aimed primarily to examine the relationship between Allah centeredness and moral disengagement. The second aim of the study was to examine the relationship of both variables with demographic variables such as gender and, age, and marital and educational status. The study was conducted using, a relational screening model and descriptive analyzes, and consisted of 502 participants, aged between 16 and 70 who had graduated from primary/secondary school, high school, university or from second or third cycle degree programs. The data collection process of the study was performed using at demographic information form, Scale of Allah Centeredness, and Scale of Moral Disengagement. In the study, a negative significant relationship was found between Allah centeredness and moral disengagement. It was also found that the explanatory effect of Allah centeredness on moral disengagement was 5.6%. Significant relationships were detected between Allah centeredness and moral disengagement variables and age, gender, and educational status. The findings were compared with the literature data in the discussion section, and interpretations and recommendations were made.